Management of interest rate risks in economic institutions - Kouider, Ibtissem (The International tax journal, 2025)
The study aims to present the various mechanisms and strategies that help economic institutions to cover interest rate risks resulting from sudden and unfavorable fluctuations in these prices, which affects the financial positions of these institutions, whether they are lenders or borrowers, and therefore some techniques and means must be used to reduce these risks. In this regard, we find the contracts negotiated in the consensual markets, which include contracts with fixed terms and optional contracts (CAPS, FLOORS and CALLARS), in addition to contracts negotiated in the regulated market, as is the case in the French international futures market, which includes a variety of products that guarantee coverage of interest rates in the currency Consolidated (Euro), this assortment mainly includes forward contracts and options for interest rates expressed in Euros, allowing economic institutions to manage and manage interest rate risks in an effective manner.